Replacing vaccine paper package inserts: a multi-country questionnaire study on the acceptability of an electronic replacement in different target groups - Martina Bamberger; Hans De Loof; Charlotte Marstboom; Stéphanie Oury; Paolo Bonanni; Odile Launay; Mira Kojouharova; Pierre Van Damme (BMC, 2022)
Abstract Background In the European Union it is mandatory to include paper package leaflets (PPL) with all medicines, including vaccines, to inform the recipient. However, it is difficult to meet the necessity for localized PPLs in each of the 24 official European languages. Replacing PPLs with electronic versions offers many advantages including redistribution across nations, reduced storage space, accessibility by the visually impaired, easily updated information or the addition of video content. We wanted to assess the attitudes of patients (vaccine recipients or their parents) to the potential of replacing PPL with electronic versions. Methods We surveyed vaccinees or their parents in four European countries-Belgium, Italy, Bulgaria and France-for their actual use of vaccine PPLs and their opinions about switching to an electronic package leaflet. Our survey was conducted online because of the COVID-19 pandemic and resulted in 2518 responses to a questionnaire targeted at three specific groups with particular information needs: parents of young children, pregnant women and the elderly (≥ 60 years). Results Our main findings are that currently vaccine PPLs are rarely used and frequently unavailable for the vaccinee. Across the four countries surveyed 55-82% of vaccinees would accept an electronic version, as did 64% when there was an option to request a printout of the leaflet. Conclusions We found that switching to electronic versions of vaccine PPLs is an acceptable alternative for the public, potentially increasing the quality and amount of information reaching vaccinees while eliminating some barriers to redistribution of vaccines between countries.